India‐Asia convergence: Insights from burial and exhumation of the Xigaze fore‐arc basin, south Tibet. Issue 5 (11th May 2017) - Li, Guangwei; Kohn, Barry; Sandiford, Mike; Xu, Zhiqin
Abstract: The composite fore‐arc/syncollisional Xigaze basin in south Tibet preserves a key record of India‐Asia collision. New apatite fission track and zircon (U‐Th)/He data from an N‐S transect across the preserved fore‐arc basin sequence near Xigaze show a consistent northward Late Cretaceous to middle Miocene younging trend, while coexisting apatite (U‐Th‐Sm)/He ages are all Miocene. Corresponding detrital zircon U‐Pb data are also reported for constraining the Cretaceous depositional ages of the Xigaze basin sequence in the region. Thermal history modeling indicates that the basin experienced northward propagating episodic exhumation, along with a northward migration of the depocenter and a pre‐existing Cenozoic syncollisional basin sequence which had been removed. In the southern part, fore‐arc exhumation commenced in the Late Cretaceous (~89 ± 2 Ma). Following transition to a syncollisional basin in the Paleocene, sedimentation in the central and northern Xigaze basin continued until the latest Eocene (~34 ± 4 Ma). Ongoing folding and thrusting (e.g., Great Counter Thrusts) caused by progressive plate convergence during late Oligocene‐early Miocene time resulted in regional uplift and considerable basin denudation, which fed two fluvial basins along its northern and southern flanks and exposed the basement ophiolite. Subsequent incision of the Yarlung River resulted in Miocene cooling in the region. Different episodes in the exhumation history of the Xigaze basin, caused by thrusting of an accretionary wedge and ophiolitic basement, can be linked to changes in India‐Asia convergence rates and the changing subduction pattern of the Indian and Neo‐Tethyan slabs. Key Points: Northward younging trend in cooling ages of Xigaze fore‐arc basin Exhumation history linked to changes in India‐Asia convergence rates Sedimentation in Xigaze basin probably continued until latest Eocene